Comparative Evaluation of Nutritional Composition, Fatty Acid Profile and Sensory Attributes of Commercial Plant-Based Meat Analogues and Chicken Nuggets - , Aaliya Tahseen, Sathu. T, Muthukumar Muthupalani, Vasudevan. V. N., Irshad. A, Preethy John, K. Raji, MHS Abrar Basha (Archives of Current Research International, 2024)
This study provides a comprehensive evaluation of the proximate composition, fatty acid profile, and sensory attributes of commercial plant-based meat analogue (PBMA) nuggets compared to traditional commercial chicken nuggets. Fatty acid methyl esters (FAMEs) of the samples were prepared for analysing the fatty acid profile. Nutritional analysis revealed that PBMA nuggets contain higher levels of polyunsaturated fatty acids (PUFAs), ranging from 18.92% to 45.97%, and lower levels of saturated fatty acids (SFAs), with a maximum of 47.61%, potentially offering cardiovascular benefits. Notably, PBMA nuggets are cholesterol-free, while chicken nuggets exhibit cholesterol levels ranging from 50.69±0.37 mg/100g to 54.74±0.31 mg/100g. Total phenolic content (TPC) analysis showed that PBMA nuggets possess superior antioxidant capacity, with TPC values ranging from 2.00±0.02 to 2.94±0.02 mg gallic acid equivalent (GAE)/g, compared to chicken nuggets, which have TPC values of 0.913±0.02 and 1.23±0.03 mg GAE/g. Physico-chemical assessments indicate that PBMA nuggets generally have lower moisture content (46.69±0.11% to 51.87±0.12%) and protein content (5.15±0.04% to 12.12±0.03%) but higher fat (11.43±0.02% to 18.21±0.05%), fibre (1.09±0.02% to 1.20±0.02%), carbohydrate (21.12±0.06% to 28.89±0.13%), and ash content (1.94±0.007% to 3.83±0.02%) compared to chicken nuggets. Sensory evaluation revealed that chicken nuggets scored significantly higher in appearance (7.75±0.16), texture (7.25±0.16), juiciness (7.75±0.16), and overall acceptability (7.25±0.16) compared to PBMA nuggets. Despite their nutritional advantages, PBMA nuggets did not meet the sensory attributes of chicken nuggets, with lower scores in key sensory parameters. This indicates that while PBMA nuggets offer a healthier, plant-based alternative with beneficial nutritional profiles, further research and development are necessary to enhance their sensory attributes to better meet consumer preferences and expectations.